Lights at the end of the tunnel: The incidence and characteristics of recovery for Australian threatened animals. (March 2023) - Woinarski, John C.Z.; Garnett, Stephen T.; Gillespie, Graeme; Legge, Sarah M.; Lintermans, Mark; Rumpff, Libby
Abstract: Recovery of threatened species is a widely recognised conservation goal. We assess the incidence and characteristics of recovery for threatened Australian animals from the establishment of Australia's national environmental legislation in 2000 to 2022. Formal de-listings have been few, and mostly not indicative of actual recovery. However, we assessed that 29 taxa (1 fish, 4 frogs, 1 reptile, 8 birds and 15 mammals), representing 6.5 % of the 446 species that we consider were justifiably listed as threatened, have recovered over this period such that they no longer meet the eligibility criteria for listing as threatened. Most of the recovered species are mammals whose previous decline was due to introduced predators. Their recovery has been enabled by sustained management actions (establishment of predator-free havens, translocations and predator control). The lack of recovery of invertebrates is possibly because these have received little conservation investment. The limited recovery of fish is due to limited capacity for abating the threats of introduced fish predators and of exploitation and degradation of aquatic systems. Species threatened by habitat loss and degradation, fire and climate change are under-represented in recoveries. De-listing of the taxa that we assess here to have recovered would provide a tangible recognition and indicator of conservation success and help maintain the integrity of the threatened species list. However, most of the recovered species would rapidly become eligible for re-listing should their conservation management be withdrawn. Although there is a prevalent trend for decline of Australia's threatened species, these recoveries merit recognition.